Crystallization and preliminary X‐ray crystallographic analysis of polyphenol oxidase from Juglans regia (jrPPO1). Issue 6 (1st June 2014) - Zekiri, Florime; Bijelic, Aleksandar; Molitor, Christian; Rompel, Annette
<x xml:space="preserve">Abstract</x> Tyrosinase is a type 3 copper enzyme that catalyzes the ortho‐hydroxylation of monophenols to diphenols as well as their subsequent oxidation to quinones, which are precursors for the biosynthesis of melanins. The first plant tyrosinase from walnut leaves (Juglans regia) was purified to homogeneity and crystallized. During the purification, two forms of the enzyme differing only in their C‐termini [jrPPO1(Asp101–Pro444) and jrPPO1(Asp101–Arg445)] were obtained. The most abundant form jrPPO1(Asp101–Arg445), as described in Zekiri et al. [Phytochemistry (2014), 101, 5–15], was crystallized, resulting in crystals that belonged to space group C121, with unit‐cell parameters a = 115.56, b = 91.90, c = 86.87 Å, α = 90, β = 130.186, γ = 90°, and diffracted to 2.39 Å resolution. Crystals were only obtained from solutions containing at least 30% polyethylene glycol 5000 monomethyl ether in a close‐to‐neutral pH range.